Lieux vénérés puis oubliés : L’exemple de mémoires familiales manouches - Jean-Luc Poueyto (Bulletin de l’Association de Géographes Français)
The Manouches, although for the most part belonging to the “Gens du voyage” French category, are not wanderers. They are very attached to certain territories, those in which they live, those in which their missing ancestors lived, those in which those ones are buried. However they travel or are displaced, these families maintain complex and intense relationships with these places of life and death, being divided between the need to anchor in a family memory and that of break free from it.